'Healthy Publics' and the pedagogy of It's a Sin. (February 2023) - Ledin, Chase; Weil, Benjamin
The UK television series It ' s a Sin (2021) emerged alongside ongoing cultural projects that re-script acquired immunodeficiency syndrome crisis narratives and contribute to a broader 'post-acquired immunodeficiency syndrome' media culture. In this Cultural Commons piece, we consider how community health promoters have adapted the imagery from It ' s a Sin to create new human immunodeficiency virus educational materials. We situate these media practices in relation to an ongoing practice to think about the 'end of acquired immunodeficiency syndrome' through strategic health communication practices and question the cultural significance of adapting It ' s a Sin for health advocacy initiatives. We argue that more attention needs to be paid to the exchanges between popular culture and health promotion imagery. Critical health and media scholars should develop more complex cultural health criticism to capture the exchanges between health promotion and melodrama, to create accountability and avoid re-scripting normative perspectives of health and illness within post-acquired immunodeficiency syndrome media.